PENGARUH PENAMBAHAN SERAT PANDAN PUNDAK DURI (PANDANUS TECTORIUS) TERHADAP KUAT TARIK BELAH BETON - Sherly Marlia; Agustin Gunawan; Fepy Supriani (Inersia: Jurnal Teknik Sipil, 2019)
Concrete is a material that is high in compression, but weak in tensile. The weakness of concrete can be minimized by conducting several concrete development. Fiber-reinforced concrete is concrete given the addition fiber in the concrete mixture. Pandanus tectorius spines fairly high in fiber, so that should be developed in the technology of materials, particularly concrete engineering fields. This study aims to determine the value of tensile strength of concrete sides and variations of the fiber increment persentage in the concrete that would get the highest tensile strength. Tested specimen for tensile strength was cylindrical with 30 cm in height and 15 cm in diameter.There was 4 variations of pandanus tectorius fiber addition, consecutively 0.25%, 0.5%, 0.75% and 1%. The water cement ratio used was 0,5 with slump range between 60-100 mm. The addition of pandanus tectorius fiber gave a lower tensile strength than normal concrete. The lowest and highest strength was consecutively 9,687%(variation 0,25%) and 25,718% (variation 1%).